#93: Is There a Role for Letermovir for CMV Prophylaxis in Pediatric Solid-organ Transplant Recipients: Retrospective Study of Premature Discontinuation of Planned Valganciclovir Prophylaxis Linked to Myelosuppression. (26th March 2021) - Joseph, T; Muller, W; Heald-Sargent, T; Herold, B
Abstract: Background: Cytomegalovirus (CMV) disease continues to be a major cause of morbidity and mortality in patients who receive solid-organ transplants (SOT). The effectiveness of the primary drugs used for CMV prophylaxis, oral valganciclovir or intravenous ganciclovir (v/GCV) may be limited by their myelosuppressive toxicity, and less commonly, nephrotoxicity. Intolerance of these drugs may result in premature discontinuation of CMV prophylaxis, or other myelosuppressive agents such as trimethoprim–sulfamethoxazole (TMP-SMX). Letermovir is approved for CMV prophylaxis in adult stem-cell transplantation. The drug inhibits the CMV–terminase complex and is not myelosuppressive. However, there are no studies of this agent in pediatric SOT recipients, and its potential role in pediatric SOT patients is unknown. To address this knowledge gap, we propose to conduct a multi-center retrospective study to assess the frequency of neutropenia and lymphopenia during v/GCV prophylaxis, and other associated complications in SOT patients receiving v/GCV. In preparation, we conducted a pilot study at two centers to determine sample size and optimize the data collection methods. Methods: Electronic medical record data from pediatric (<18 years at the time of transplant) SOT recipients who were treated with v/GCV prophylaxis and transplanted between January 1, 2016, and December 31, 2018, were reviewed from the time of transplant to 12 months post-transplant. Data from 31 patients followed at CHAM (17 liver, 8 heart, 4 kidney, 2 kidney–liver) and 15 patients at Northwestern (5 liver, 3 heart, 7 kidney) are included here. These data provide the framework for a planned St. Jude-PIDS transplant network study, which will be supported by Merck. Results: At least one episode of neutropenia (defined as Absolute Neutrophil Count (ANC) less than 1000 cells/mm 3 ) was documented in 23/46 (50%) (16 at CHAM and 7 at Lurie) while on v/GCV prophylaxis. At CHAM, 25/31 (81%) of patients had at least one episode of lymphopenia (defined as absolute lymphocyte count (ALC) less than 1000 cells/mm 3 ) while receiving v/GCV post-transplantation. The number of patients for whom v/GCV was held or discontinued prior to completion of a planned prophylactic course was 24/46 (18/31 (52%) at CHAM and 6/15 (40%) at Lurie. Moreover, 9/31 (29%) patients at CHAM were switched from TMP-SMX to alternative Pneumocystis jiroveci (PJP) prophylaxis. The percentage of patients who had CMV DNAemia after discontinuation of v/GCV at CHAM was 16/31 (52%). Conclusions: Our pilot data suggest that v/GCV and/or TMP-SMX are frequently discontinued or held because of neutropenia or lymphopenia, which may expose patients to increased risk of subsequent CMV DNAemia or disease. Full data from all sites will also include changes in renal function, other opportunistic infections, differences in immunosuppression, and episodes of graft rejection.